UV-B Radiation Impacts Shoot Tissue Pigment Composition in Allium fistulosum L. Cultigens - Kristin R. Abney; Dean A. Kopsell; Carl E. Sams; Svetlana Zivanovic; David E. Kopsell (The Scientific World Journal)
Plants from the Allium genus are valued worldwide for culinary flavor and medicinal attributes. In this study, 16 cultigens of bunching onion (Allium fistulosum L.) were grown in a glasshouse under filtered UV radiation (control) or supplemental UV-B radiation [7.0 μmol·m−2·s−2 (2.68 W·m−2)] to determine impacts on growth, physiological parameters, and nutritional quality. Supplemental UV-B radiation influenced shoot tissue carotenoid concentrations in some, but not all, of the bunching onions. Xanthophyll carotenoid pigments lutein and β-carotene and chlorophylls a and b in shoot tissues differed between UV-B radiation treatments and among cultigens. Cultigen “Pesoenyj” responded to supplemental UV-B radiation with increases in the ratio of zeaxanthin + antheraxanthin to zeaxanthin + antheraxanthin + violaxanthin, which may indicate a flux in the xanthophyll carotenoids towards deepoxydation, commonly found under high irradiance stress. Increases in carotenoid concentrations would be expected to increase crop nutritional values.